Factors associated with the frequency of medical consultations by older adults: a national study - Joyce Grabher Meier; Luciane Patrícia Andreani Cabral; Camila Zanesco; Clóris Regina Blanski Grden; Cristina Berger Fadel; Danielle Bordin (SciELO, 2020)
Abstract Objective: To analyze factors associated with the high frequency of medical consultations (five or more consultations) among older adult participants of the National Health Survey - 2013. Method: A quantitative cross-sectional study conducted with data from individuals aged 60 years and over (n = 19,503). The outcome variable came from the question: 'How many times have you consulted the doctor in the last 12 months? Fifty-seven (57) independent variables were listed. The Waikato Environment for Knowledge Analysis software program was used in the analysis. The data set was balanced and the dimensionality reduction test was performed. The variables which were strongly related to the dependent variable were analyzed using logistic regression. Results: The independent variables listed were strongly related to the outcome variables: female gender, negative self-perception of health condition, inability to perform usual activities for health reasons, diagnosis of chronic disease, seeking health services for health-related care, and hospitalization. Conclusion: The results reflect the relevance of expanding and qualifying services through effective prevention, protection and health promotion actions.